Recent trends in image processing and pattern recognition : first International Conference, RTIP2R 2016, Bidar, India, December 16-17, 2016, Revised selected papers /: first International Conference, RTIP2R 2016, Bidar, India, December 16-17, 2016, Revised selected papers. (2017) - Unknown
No abstract available